Boosting lily bulblets production: a study on the effects of 6-benzylaminopurine and silver nanoparticles - Oscar Tomanguilla-Llanos; Jegnes Benjamín Meléndez-Mori; José Jesús Tejada-Alvarado; Yoiner K. Lapiz-Culqui; Eyner Huaman-Huaman; Marileydi Zuta-Puscan; Reyna Stefani Mego-Pérez; Manuel Oliva-Cruz (Scientific Reports)
Abstract The lily stands out as one of the most economically relevant flowers worldwide and enjoys great popularity as a cut flower in the florist industry. This prominent position underlines the need to implement and continuously improve sustainable protocols that ensure its efficient production, multiplication and conservation. In this context, the present study aimed to investigate the potential biostimulant effect of Silver Nanoparticles (AgNPs) and 6-Benzylaminopurine (BAP) on two lily cultivars (Lilium LA Hybrid ‘Hyde Park’ and Lilium LA Hybrid ‘Yellow Diamond’), through their individual and combined application. The research focused on evaluating the influence of these treatments on two key aspects: (1) regeneration capacity and bulblet development from bulb scales, and (2) morpho-physiological growth parameters in regenerated plants. Analysis of the results revealed several significant effects of the interaction between AgNPs and BAP on different regeneration and growth parameters in two lily cultivars. In cv. ‘Hyde Park’, the combination of AgNPs at 50 mg L−1 with BAP at 200 mg L−1 increased bulblet number to an average of 5.6. In cv. ‘Yellow Diamond’, the application of AgNPs at 50 mg L−1 without BAP and the combined treatment of AgNPs at 100 mg L−1 with BAP at 200 mg L−1 produced a higher number of bulblets (3.2). The highest bulblet weight in both cultivars was obtained with the combination of AgNPs at 100 mg L−1 and BAP at 50 mg L−1. Plant height also varied considerably; in cv. ‘Hyde Park’ the tallest plants (greater than 140 mm) were recorded under treatment with BAP at 50 mg L−1 without AgNPs, while in cv. ‘Yellow Diamond’, the largest plants (greater than 100 mm) were observed with the application of AgNPs at 100 mg L−1 without BAP. In terms of physiology, the SPAD index did not show significant improvements compared to the control group. In conclusion, the results indicate that the impact of the interaction between AgNPs and BAP is concentration, cultivar, and measured variable dependent, suggesting a varietal-specific response and the possibility of both beneficial and adverse effects on different aspects of lily development. This underscores the importance of carefully adjusting doses and combinations to optimize regeneration and plant growth.